STUDY OF EFFECT OF DISTANCE AND ORIENTATION OF DISCONTINUE LAYERS ON ROCK USING DRAG PICK IN LABORATORY WITH NUMERIC MODELING - MADE MAHENDRAYANA (NIM : 12112014), I
Mining process is basically the process of taking valuable materials (ore) that are under the surface of the earth to be processed into goods that are useful. To extract the precious material (ore), firstly, the miner must "remove" the valuable material that covers it. Therefore, a process of excavation of the cover material is made so that the desired valuable material can be exposed, taken and utilized. This study discusses the mechanical rocking with the type of dug drag pick teeth. This study used a sample grouped by distance and orientation of discontinu field in laboratory scale with dimensions of 100 x 60 x 15 cm. The first sample group was formed in the form of gypsum block with variation of 5 cm, 10 cm and 15 cm with orientation 90 Ã‚Â° and second group has variation of discontinuous field orientation of 45 Ã‚Â° and 135 Ã‚Â° with distance of 10 cm. From the discussions that have been made to the results of the tests, both laboratory tests and numerical modeling, it can be concluded that: From the test it is found that the value of cutting force increases with increasing discontinuous field distance; From the test we get cutting force value for rock samples with discontinuous field orientation of 45⁰ larger than rock samples with discontinuous field orientation of 135⁰ in this study; The result of numerical simulation shows the same tendency as the laboratory test but the value of laboratory test result style is bigger than the cut style from the numerical modeling.